INDEKS ENTOMOLOGI VEKTOR NYAMUK Aedes spp. DI DAERAH ENDEMIS DEMAM BERDARAH DENGUE (DBD) - Yudi Yahya (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2024)
Dengue Hemorrhagic Fever (DHF) in Indonesia remains a major health problem and has shown fluctuating incidence rates over the past 10 years. This study aims to determined the entomological index of Aedes spp mosquito vectors in the DHF endemic area of Sungai Andai Village, North Banjarmasin District, Banjarmasin City. The study was conducted from May to June 2021 using a cross-sectional method. The research location was in the DHF endemic area of Sungai Andai Village. The survey was conducted using the single larvae method and the eggs were collected by ovitraps. Entomological data were analyzed descriptively. Based on the Maya index, 87.14% of houses were categorized as low risk and 12.86% as medium risk for mosquito breeding sites. Sungai Andai Village had a Larva-Free Rate of 81.43%; House Index of 18.57%; Container Index of 2.38%; Breteau Index of 21.43%; Pupae Index of 4.29%; Density Figure of 4; and Ovitrap Index level of 1-2. Sungai Andai Village is at medium risk as a breeding site for Aedes spp, thus necessitating efforts for the prevention and control of DHF transmission.